2019
DOI: 10.1242/bio.041699
|View full text |Cite
|
Sign up to set email alerts
|

Karyoevolution ofCrenicichlaheckel 1840 (Cichlidae, Perciformes): a process mediated by inversions

Abstract: Crenicichla (Cichliformes, Cichlidae) present a highly conserved diploid number 2n=48 with fundamental numbers varying between 52 and 62. We analyzed four species in order to investigate the role of repetitive DNA in chromosome evolution in the genus. Crenicichla johanna , Crenicichla cf. saxatilis and Crenicichla cf. regani have 2n=48 (8 m/sm and 40st/a) and FN=56, while Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Furthermore, in the larger homolog of this pair, an extra site at the opposite end was recorded. This result can be explained by the amplification of 45S rDNA motifs, with subsequent uneven crossing-over between them, similar to that observed in fish [ 41 ], amphibians [ 42 ], plants [ 43 ] and other arthropods [ 15 , 44 ]. The amplification of 45S rDNA is a phenomenon epigenetically controlled by the cell and may constitute a response to environmental factors [ 45 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, in the larger homolog of this pair, an extra site at the opposite end was recorded. This result can be explained by the amplification of 45S rDNA motifs, with subsequent uneven crossing-over between them, similar to that observed in fish [ 41 ], amphibians [ 42 ], plants [ 43 ] and other arthropods [ 15 , 44 ]. The amplification of 45S rDNA is a phenomenon epigenetically controlled by the cell and may constitute a response to environmental factors [ 45 ].…”
Section: Discussionsupporting
confidence: 72%
“…The amplification of 45S rDNA is a phenomenon epigenetically controlled by the cell and may constitute a response to environmental factors [ 45 ]. In some organisms, such as plants [ 46 ], mammals [ 47 ] and fish [ 41 ], it has been demonstrated that 45S rDNA constrictions constitute sites prone to breakage and can promote genomic instability. During the meiotic bouquet, the chromosome ends and joins the nuclear membrane, and the telomeres remain clustered at a single pole of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its conserved character, the 5S rDNA has been widely used as a marker in molecular cytogenetics for the characterization of various species. Most of the investigated karyotypes have relatively few (often just one) 5S rDNA loci (Sochorová et al, 2018;Frade et al, 2019). The 5S rDNA has been reported to co-localize with other multigenes, such as histones genes and small nuclear RNAs (snRNAs) of the U family (Novotná et al 2011;Piscor et al, 2018); these associations seem to indicate an old and linked organization of such sequences in the genomes of the relevant species (Cabral-de- Mello et al, 2011).…”
Section: Introductionmentioning
confidence: 99%